The Extent to which the Trademark may be Transacted Separately from the the Commercial Store - Latif, Adnan Baqi (Journal of Legal and Political Studies, 2016)
It is essential to know that sale transactions are not limited to tangibles, but they encompass financial rights including trademark as an intangible right which is attached to the financial responsibility of the owner like other types of properties, allowing the owner to transact with it. However, the question that arises is the possibility of transferring the trademark separate from the "GoodWill”, emphasizing that trademark is not a separate property from the "GoodWill”, but it is attached to it.Throughout this comparative study titled (To what Extent it is Possible to transact with the Trademark Separate from the "GoodWill” one can realize how comparative jurisdictions are divided about this issue. According to some of these jurisdictions, it is not permitted to transact with the trademark separate from the "GoodWill” and such a direction is supported by the judiciary. This was the view of the Iraqi Trademark and Data Law (amended) in Articles 17 and 18, and the Egyptian Trademark and Data Law (abolished) No. 57, 1939 in Article 18. In the past, courts in the United States and the United Kingdome also applied this view. The justification for such a ban was to protect consumers from confusion and beguilement which may result from selling the trademark separate from the "GoodWill”, because customers still believe that the products which bear the trademark is still part of the project that the owner has already waived.On the other hand, the current widespread view, according to many national and international jurisdictions, believes that trademark can be sold in separation with the "GoodWill”. The reason for adapting such a view by these jurisdictions is the necessity of trade, especially the new globalization system and the advent of the World Trade Organization. In addition, another reason is the consequences of strict application of the ban rule, which constituted a hurdle to the development and expansion of "GoodWill”. The benefits of selling trademark in separation with the "GoodWill” and its direct influence on financial aspects of the "GoodWill”, and increasing income and reducing expenditures are also reasons for such a view.The article concludes by analyzing how national and international comparative legislations accepted these new situations and allowed selling the trademark in separation with the "GoodWill”. In contrast to this view, the Iraqi legislature is still applying the ban rule. Even though this position contradicts with the principles of the TRIPS Agreement and does not serve Iraq in its attempt to be a member of the World Trade Organization. Accordingly this study suggests that the Iraqi legislature change the ban rule.
Keywords: Transaction; Trademark; financial responsibility; GoodWill